Administrator Leadership Characteristics Factors That Effects to Administration Success of the “1 District, 1 Quality School” Under the Surin Primary educational Service Area Office: Administrator Leadership Characteristics Factors That Effects to Administration Success of the “1 District, 1 Quality School” Under the Surin Primary educational Service Area Office - Kongdee, Walailak; Poldech, Sripen; Kultanan, Phatchanee (RATANABUTH JOURNAL, 2025)
The purposes of this research article were to study 1) the level of factors in the characteristics of administrators, 2) the level of success in 1 District, 1 Quality School administration, 3) the relationship between the administrator’s characteristics factors and the success in 1 District, 1 Quality School administration, and 4) to construct an equation for predicting success in 1 District, 1 Quality school administration under the Surin Primary Educational Service Area Office The sample consisted of 175 School directors and teachers by using a Multi-stage Sampling. Research tools were estimation scale questionnaire The data were analyzed by percentage, mean, standard deviation, Pearson Correlation Coefficient and Multiple Regression Analysis. The results showed that 1) Administrator Leadership Characteristics Factors That Effects to Administration Success of the “1 District, 1 Quality School” under the Surin Primary Educational Service Area Office in overall were at a high level 2) Success in “1 District, 1 Quality School” under the Surin Primary Educational Service Area Office in overall was at a high level 3) Factors in all aspects of administrator’s characteristics related to success in "1 District, 1 Quality School" under the Surin Primary Educational Service Area Office statistically significant at the .01 level 4) The forecast equation by using stepwise regression analysis found that there were 4 aspects that can predict the administrator leadership characteristics factors that effects to administration success of the"1 District, 1 Quality School" under the Surin Primary Educational Service Area statistically significant at the level of .05 was the communication skills, Administrative skills, Vision and Leadership aspect was able to predict success in "1 District, 1 Quality School" administration at 85.60 percent. The forecast equation in raw score form was = 1.035+ .244XX6 + .212XX1 + .191XX2+. 130XX3 and the forecast equation in standard score form was = .298ZX6+ .276ZX1+ .237ZX2.171ZX3